Kebijakan Penataan Ruang Terbuka Hijau di Kota Malang - Sukowati, Praptining (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2012)
The firs purpose of the research is to analyze the sustainable development policies and public participation to the Green Open Spaces shifting function in Malang. The second is to analysis the factors that binder the policy implementation process. This paper shows that public participation in the sustainable development policies is less than optimal. Some factors that impede the policy implementation are 1) inadequate provision of GOS both in quantity and quality; 2) many weakness in the institution who manage the GOS; 3) the weak role of the stakeholders; 4) the use of open land for GOS function is not optimal yet. Some of the recommendation of this research include the need to revise UU No.24/1992; to develop guidelines for the implementation of GOSs management; to improve the campaign about the importance of GOS through